Ukazanie puti v tsarstvie nebesnoe. Pouchenie (na Aleutsko-Lisʹevskom iazykie) sochinennoe sviashchennikom Ioannom Veniaminovym, 1833 goda. - Innokentiĭ, Saint, Metropolitan of Moscow and Kolomna, 1797-1879. (Moskva, Sinodalʹnaia tipografiia, 1899)
Added title-page and text in Aleut language in Church-Slavic transcription. Mode of access: Internet.